2022
DOI: 10.1227/neu.0000000000002042
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Neurological Outcomes Associated With Circulatory Shock After Moderate–Severe Traumatic Brain Injury: A TRACK-TBI Study

Abstract: BACKGROUND: Extracranial multisystem organ failure is a common sequela of severe traumatic brain injury (TBI). Risk factors for developing circulatory shock and long-term functional outcomes of this patient subset are poorly understood. OBJECTIVE: To identify emergency department predictors of circulatory shock after moderate-severe TBI and examine long-term functional outcomes in patients with moderate-severe TBI who developed circulatory shock. METHODS: We conducted a retrospective cohort study using the Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A clinical trial might compare early exposure of dexmedetomidine versus propofol in severe TBI patients and assess the development of autonomic instability-related multi-system organ dysfunction. Given the downstream morbidities associated with early circulatory dysfunction and the acute respiratory distress syndrome after TBI, 45,46 there is a large theoretical benefit in blocking or establishing prophylaxis against sympathetic hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial might compare early exposure of dexmedetomidine versus propofol in severe TBI patients and assess the development of autonomic instability-related multi-system organ dysfunction. Given the downstream morbidities associated with early circulatory dysfunction and the acute respiratory distress syndrome after TBI, 45,46 there is a large theoretical benefit in blocking or establishing prophylaxis against sympathetic hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Toro et al conducted a retrospective analysis of the TRACK-TBI database and showed that race, GCS in the emergency department, computed tomography Rotterdam scores less than 3, and development of hypotension in the emergency department were associated with developing circulatory shock and showed to be associated with poor long-term functional outcome. 42 In this same TRACK-TBI study population, Toro et al investigated the association of vasopressor choice with clinical and functional outcomes following moderate-to-severe TBI through a retrospective cohort study. 43 The study included 156 adult patients with moderate-to-severe TBI (defined as GCS score < 13) admitted to the intensive care unit (ICU) and who received intravenous vasopressors within 48 hours after ICU admission.…”
Section: Management Of Traumatic Brain Injurymentioning
confidence: 99%
“…Toro et al conducted a retrospective analysis of the TRACK-TBI database and showed that race, GCS in the emergency department, computed tomography Rotterdam scores less than 3, and development of hypotension in the emergency department were associated with developing circulatory shock and showed to be associated with poor long-term functional outcome. 42…”
Section: Management Of Traumatic Brain Injurymentioning
confidence: 99%
“…Given the data available, this is reasonable, although it is difficult to elucidate the precise mechanisms by which circulatory shock developed or whether vasopressor administration influenced outcomes. As stated by Toro et al, 6 circulatory shock likely represents a multisystemic process of dysregulation, and vasopressor administration may be one of many potential strategies to combat aberrant catecholamine release and autonomic dysfunction in the TBI population. 9 However, although maintaining an adequate cerebral perfusion pressure is essential in patients with TBI, several undergo invasive procedures such as intracranial monitor or drain placement or surgical decompression, and special care should be taken to avoid iatrogenic hypertensive episodes which could lead to intra-axial or extra-axial bleeding.…”
mentioning
confidence: 99%
“…Toro et al 6 present a multicenter retrospective study of prospectively collected data to evaluate this concept. Their article, titled “Risk factors and neurologic outcomes associated with circulatory shock after moderate-severe traumatic brain injury: a TRACK-TBI Study,” 6 presents an analysis that focuses on adults with moderate and severe TBI (Glasgow Coma Scale [GCS] score of <13) and no major extracranial injury who developed circulatory shock after hospital admission. They examine risk factors for circulatory shock after moderate-severe TBI and exlpore the association between circulatory shock and post-TBI long-term clinical and functional outcomes.…”
mentioning
confidence: 99%